DIAGNOSIS AND MANAGEMENT DIVERTIKULUM MECKEL - I Made Peri Ardiana Kusuma (E-Jurnal Medika Udayana, 2013)
Meckel Divertikulum is a congenital abnormality from gastrointestinal tract that commonly found with prevalence 2%, caused by failure of closure and reabsorption of omphalomesenteric duct. This failure also can lead info umbilicoileal fistule, omphalomesenteric duct sinus, omphalomesenteric duct cyst, and fibrotic band. Mostly this disease is asymptomatic. Its symptomatic caused by the complications, intestine obstruction (35%), bleeding (32%), diverticulum (22%), umbilical abnormality (10%), hernia littre, and neoplasm. Meckel Diverticulum usually found incidentally caused by its asymptomatic characteristic. Meckel Scanning is the most accurate supporting examination for Meckel Diverticulum with scintyscan technetium-99m pertechnetate. Another imaging modality can be used as indication and its availability. Definitive therapy for this congenital abnormality is surgery. There are four surgery technic to treat Meckel Diverticulum, diverticulectomy closured-suture based, wedge resection of intestine wall with diverticulum closured-suture based, segmental resection of intestine include diverticulum and end-to-end anastomose, and division of fibrotic band with or without diverticulectomy.